Antimicrobial resistance: A new threat in the COVID-19 era? - Laura-Larisa Dracea (Amaltea Medical Publishing House, 2021)
During the COVID-19 pandemic antibiotic use considerably increased being partially justified by the fear of bacterial infection. Antibacterial resistance (ABR), due to increased and unjustified antibiotic use, is a major threat to the economy and global health. In pediatric practice, antibiotics are the most common prescribed substances, both in the community and hospital setting. Unjustified use, inappropriate doses and prescription duration promote antibacterial resistance and increase mortality. The majority of current health problems in children are viral infections, even the rates of infection are higher as in adults, fact that determines more frequent diagnostic uncertainties. More so, respiratory infections in children have a greater potential of excessive and incorrect use of antibiotics, that justifies protocol based evaluations, risk assessment and targeted treatment. The diversity and magnitude of clinical presentation of SARS-CoV-2 infection, along with early and long-term complications and sequellae, also noticed in pediatric practice, created the premises of increased use of antibiotics, aggravating the ABR. This is a challenge for the clinician during a period when development of new antibiotics is not a priority of the pharma industry anymore. Research of mechanisms that contribute to ABR, innovative therapies, expansion of genetics and implementation of antibiotic stewardship, together with stimulating pharma industry for developing of new substances, may have the potential of decreasing antibacterial resistance in an era of medical and economic uncertainties generated by the COVID-19 pandemic.